Nutrition care quality indicators in hospitals and nursing homes: A systematic literature review and critical appraisal of current evidence. Issue 6 (June 2020) - Moick, S.; Simon, J.; Hiesmayr, M.
Summary: Objective: Quality indicators (QIs) can be used to assess and improve the quality of care in health care institutions. Although QIs about nutrition care in hospitals and nursing homes have been used in studies, no systematic catalogue exists to date. This systematic literature review identifies nutrition care QIs in hospitals and nursing homes and maps them according to QI type, stakeholder level and nutrition care theme. We also assess the level of consensus between studies and critically appraise the QIs presented therein based on two conceptual frameworks. Methods: Ovid, Scopus and grey literature were searched from 1995 to 2016 including studies in English and German. Papers were considered if they presented, developed, assessed, rated or applied nutrition care QIs in hospitals or nursing homes. We used Donabedian's framework to define structure, process and outcome indicators, the WHO (World Health Organization) definition to describe stakeholder levels, and a structured table to map indicators within themes. Further, we used the Institute of Medicine (IOM) and the Organisation for Economic Cooperation and Development (OECD) frameworks' key dimensions to measure the conceptual quality of the QIs. Results are summarised and presented tabulated and narratively. Results: From 536 identified studies, 46 were included. Eight hundred and twenty-two QIs were extracted and mapped into 19 themes and 151 sub-themes. Half were process indicators (49%) and about a quarter were outcome (28%) and structure (23%) indicators, respectively. The vast majority (71%) targeted micro level, while 28% meso level and only 1% macro level information. The nutrition themes meals/mealtimes (12%), treatment (adherence) (12%), nutrition screening (7%), assessment (7%) and monitoring (7%) were most frequently covered. 69% of indicators were cited by more than one study. Most frequent framework dimensions were patient-centeredness (33%), timeliness (30%), validity (30%) and actionability/feasibility (30%). Conclusion: The large number of nutrition care QIs in hospitals and nursing homes indicates the high interest in and importance of better nutrition care provision in institutions. However, the great variability indicates little consensus of the nutrition community on how to best assess and measure the quality of nutrition care. The limited methodological and conceptual validity of presented QIs and the low representation of QIs at macro and meso levels make international consensus finding complicated. Increased efforts including all stakeholder levels and using conceptual frameworks to define a limited number of key QIs with high methodological validity, actionability and stakeholder relevance are needed. Registration in clinicaltrials.gov: Identifier: NCT02820246 .